(untitled) (Research, Society and Development, 2023)
• Objective: The aim of this study is to understand the theme of vertical transmission and the possible pathological outcomes in neonates caused by SARS-CoV-2 and to verify that the infection is associated with a greater risk of any respiratory disorder and some other neonatal morbidities, but which hardly lead to to mortality. Methodology: deals with an integrative review from March to April 2022, in the SciELO, Lilacs and PubMed databases using the terms COVID-19, newborns, SARS-CoV-2, neonates, in accordance with the classification of descriptors in Health Sciences. The inclusion criteria were: articles published in Portuguese, English and Spanish between 2020 and 2021. Results: One hundred and seventy-seven articles were found, which were submitted to inclusion criteria, leaving only eleven that worked with the proposed theme, which were analyzed individually. Conclusion: in the works it was verified that it has not yet been possible to verify the vertical and transplacental transmission of SARS-CoV-2 and the symptoms are still nonspecific, which still shows several gaps when it comes to the relationship between neonates and COVID-19. Therefore, prevention must be an essential factor and more studies must be carried out in order to provide an explanation for these various issues regarding vertical transmission and symptomatology.